1013How has change in gestational diabetes diagnosis affected pregnancy outcomes?. (2nd September 2021) - Randall, Deborah; Morris, Jonathan; Kelly, Patrick; Glastras, Sarah
Abstract: Background: Gestational diabetes mellitus (GDM) incidence is increasing in Australia, influenced by new diagnostic criteria gradually implemented from 2011. We aimed to identify whether the change was associated with increased obstetric intervention and/or improved outcomes. Methods: Linked perinatal, hospital and deaths data from New South Wales identified singleton births, 33-41 weeks, 2006-2015. Adjusted Poisson modelling predicted the GDM incidence trajectory post-2011 without the diagnostic change and estimated the post-2011 "additional GDM" cases. Actual rates of interventions and outcomes for GDM-diagnosed pregnancies were compared with predicted scenarios where the "additional GDM" group was assumed to have the same rate as (ie clinically same as): (A) the "previous GDM" group <2011; (B) the "non-GDM" group <2011; or (C) the "non-GDM" group ≥2011. Results: GDM incidence more than doubled over the study period. Actual planned birth, Caesarean and macrosomia rates were consistent with Scenario A, ie higher intervention rates, but lower macrosomia than B and C. Neonatal hypoglycaemia was lower than Scenario A, closer to B and C. Actual perinatal deaths were lower than predicted by all scenarios, showing improvement for all with GDM, not only "additional" cases. Maternal and neonatal morbidity rates were within the confidence bounds for all three predicted scenarios. Conclusions: Our study suggests that the widely adopted new diagnostic criteria for GDM are associated with increased obstetric intervention rates and lower macrosomia rates but with no clear impacts on maternal or neonatal morbidity. Key messages: A diagnostic criteria change has identified more GDM pregnancies without clear benefit for outcomes.